Building organizational resilience through sensemaking: The case of climate change and extreme weather events - Tisch, D.; Galbreath, Jeremy (Wiley Interscience, 2018)
© 2018 John Wiley & Sons, Ltd and ERP Environment. Resilience to increasingly frequent extreme weather events from climate change is of concern in many industries, especially those in the agricultural sector. This qualitative study utilizes interviews with 38 dairy farmers in New Zealand, observations recorded on site and archival documents to examine retention-enactment-selection sensemaking microprocesses thematically, and to show how sensemaking enables and constrains resilience. We found that farmers have achieved organizational resilience to extreme weather patterns during the decade to 2014 that is benign to belief in climate change; that adaptation to climate change can be anticipatory; and that social relationships in rural communities are instrumental to building organizational resilience. The implication for farmers and policy-makers is that resilience can be built by local members of rural communities in places that are familiar to them-a phenomenon we introduce as "community sensegiving." Future research directions using place-based research approaches and sensemaking concepts to build resilience are offered.